Prophylactic Use of Antibiotics in Septoplasty: is it Always Necessary - Amanat Ali Shah; Jamil, Nauman; Afridi, Jahangir Ahmad; Malik, Usman Afzal; Ahmed, Riaz; Majeed, Mian Amir (Pakistan Armed Forces Medical Journal, 2026)
Objective: To study the role of antibiotic prophylaxis in septoplasty.Study design: Quasi-experimental study.Place and Duration of Study: Department of Otolaryngology Surgery, Combined Military Hospital (CMH), Murree, Pakistan, from July 2022 to July 2024.Methodology: This study evaluated the necessity of prophylactic antibiotics in septoplasty, where a total of 60 patients, with symptomatic deviated nasal septum were randomly assigned to two groups, Group A (n=30) and Group B (n=30). Both groups received a 1.20 g test dose of intravenous (I/V) co-amoxiclav, followed by a main dose 30 minutes before surgery, while postoperatively, Group A continued with co-amoxiclav 625 mg orally every 8 hours for five days, while Group B received no further antibiotics. Clinical parameters, including pain, fever, and nasal discharge, were assessed on postoperative days 1, 7, and 14 following nasal pack removal. Statistical analysis of all collected data was done using Statistical Package for the Social Sciences (SPSS) version 26.00.Results: In Group A, 93.00% of participants experienced mild symptoms, while 7.00% had moderate symptoms. In Group B, 90.00% reported mild symptoms, while 10.00% had moderate symptoms. No cases of severe symptoms were observed in either group. Statistical analysis revealed no significant difference in symptom severity between the two groups (p = 0.64). These findings suggest that routine postoperative antibiotic use in septoplasty may not be necessary.Conclusion: Septoplasty is a clean contaminated procedure and does not need antibiotic prophylaxis in the post-operative period because of the low risk of infection.